Case report: Anesthetic management for removal of tumor thrombus in the inferior vena cava and pulmonary artery in renal cell carcinoma - Chen, Suli; Lu, Liangyuan; Zheng, Xiangli; Lin, Yanjun; Bao, Liming; Zhang, Bao; Yang, Zhanmin (Frontiers in Oncology, 2024)
Anesthetic management of patients with renal cell carcinoma with tumor thrombus in the inferior vena cava (IVC) is challenging. This paper reports the experience of anesthesia management in a patient with advanced renal cell carcinoma with thrombus accumulation in the IVC, right atrium, and pulmonary artery who underwent radical nephrectomy and tumor thrombus removal assisted by cardiopulmonary bypass. The emboli, measuring approximately 3 × 6 cm in the left inferior pulmonary artery and 4 × 13 cm in the right main pulmonary artery, were removed completely. During incision of the IVC under systemic heparinization, significant blood loss occurred in the surgical field. The surgery took 724 min, and cardiopulmonary bypass took 396 min. Intraoperative blood loss was 22,000 ml. The patient was extubated 39 hours after surgery and stayed in intensive care unit for 3 days. At 1 year follow-up, the patient was in good health and leading a normal life.